Project Based Learning Model in Improving The Ability and Trust - Desi Fitria; Mardhiyah Dwi Ilhami; Melly Susanti (International Journal of Science, Technology & Management, 2020)
Abstract. This research is focused on providing experience to teachers specifically in developing teaching materials by using project based learning. The purpose of this study is to assist teachers in improving the effectiveness and creativity of students in developing student confidence. Research and development continued with quasi-experiment in collaboration with class-room teachers. Stages of research to be carried out, namely: (1) preparation, (2) develop-ment, (3) experimental phase, (4) evaluation. The subjects of this study were teachers and students from SMKN 01, SMKN 02, SMKN 03 in Bengkulu City. Furthermore, at the implementation stage a collaborative experiment was carried out where the implementation of learning collaborates with the teacher and was designed online. The results of this study with the learning of the project model can develop students’ confi-dence and can improve students’ self-creativity.